Cyclic loading test and nonlinear analysis on composite frame consisting of steel reinforced recycled concrete columns and steel beams. (15th August 2021) - Ma, Hui; Jia, Chenjun; Xi, Jiacheng; Dong, Jing; Zhang, Xicheng; Zhao, Yanli
Highlights: Seismic behavior of the composite frame consisting of SRRC columns and steel beams was investigated under cyclic loading test. Parameter influence analysis on the mechanical behavior of composite frame. The composite frame has high horizontal bearing capacity and good deformation capacity. Abstract: A two-span and three-story of the frame specimen with a scale of 1:2.5 was tested and investigated under cyclic loading to study the seismic behavior on the composite frame consisting of steel reinforced recycled concrete columns and steel beams. After observing the loading process and failure modes, the mechanical properties of composite frame, such as the load–displacement hysteretic curves, skeleton curves, bearing capacity, interstory displacement angles, ductility, energy dissipation and stiffness degradation, were analysed in detail. On this basis, a finite element model of the composite frame which considered the constitutive properties of recycled concrete was established. The deformation diagram, stress nephogram and calculated skeleton curves of composite frame were obtained, and a nonlinear parameter analysis was also conducted. The experimental and numerical analysis results all show that the plastic hinges appeared at the end of steel beams firstly and then formed at the end of columns, which is a typical plastic hinge failure of frame. The hysteretic curves of frame are shuttle-shaped and full, and the descending section of the skeleton curves and stiffness degradation curves is relatively gentle. The average ductility coefficient, equivalent viscous damping coefficient and ultimate interstory displacement angle of frame are 3.205, 0.303 and 0.04, respectively. Therefore, the composite frame has good deformation, energy dissipation capacity and collapse resistance. The results of the nonlinear parameter analysis on the frame also exhibit that increasing the strength of steel products or recycled concrete is beneficial to the horizontal bearing capacity and lateral stiffness of frame. The maximum increase in the bearing capacity of frame can be 21.5% when the profile steel strength is increased from Q235 to Q390 and the recycled concrete strength is maintained at C40 within the parameters analysed, but the increase in material strength is unfavourable to the deformation capacity of frame. Increasing the axial compression ratio of columns in the frame obviously weakens the lateral displacement ductility of frame, which makes the frame unsafe under an earthquake. In addition, the bearing capacity and stiffness of frame increases with the increase in the linear stiffness of beams and columns. The research conclusions can provide a reference for the engineering application of this type of composite frame.